POLITICAL ECOLOGY OF GROUNDWATER: THE CONTRASTING CASE OF WATER-ABUNDANT WEST BENGAL AND WATER-SCARCE GUJARAT, INDIA - Mukherji A. (My University, 2006)
Three apparently disparate themes (groundwater, farmers and politics) interweave in this account of how groundwater-related policies in India have very little to do with the scarcity, depletion or quality of groundwater, and more to do with rural politics manifested, among other things, in terms of the presence or absence of farmer lobbies. Examples from two states of India, the water-abundant state of West Bengal and water-scarce state of Gujarat, were investigated using readily available data, analysis of the literature, interviews and fieldwork. In the case of West Bengal, although there is no pressing groundwater crisis, the government of West Bengal (GOWB) was able to successfully implement strict groundwater regulations along with a drastic increase in electricity tariff. More importantly, GOWB was able to implement these without any form of visible farmer protest, though these measures negatively affected farmer incomes. On the other hand, in Gujarat, where there is a real and grave groundwater crisis, the government of Gujarat has neither been able to implement strict groundwater regulations, nor has it been able to increase electricity tariff substantially. Thus, through the lens of ‘political ecology’ the contrasting case of these two Indian states is explained.
Keywords: GROUNDWATER RESOURCES; POLITICS; FARMER LOBBY; GUJARAT; WEST BENGAL